The Effect of Self-efficacy on Employees’ Job Satisfaction in the Post Office 40000 of Bandung City - Anisya Nurfitri Kustyani; Tjutju Yuniarsih (Budapest International Research and Critics University, 2022)
Problem studied in this study is the low job satisfaction of employees at the Post Office 40000 Bandung. This is thought to be caused by the low level of self-efficacy of the employees. This study uses a quantitative approach, with an exploratory survey method. The unit of analysis in the study was 109 employees, who came from the population. The analysis technique used is simple regression. From the results of data analysis and hypothesis testing, it was concluded that there was a positive effect of self-efficacy on employee job satisfaction at the Post Office 40000 Bandung City, in a fairly strong category.